Association of asthma with low serum vitamin D and its related musculoskeletal and psychological symptoms in adults: a case-control study - Mohammad J. Alkhatatbeh; Haneen S. Almomani; Khalid K. Abdul-Razzak; Shaher Samrah (npj Primary Care Respiratory Medicine, 2021)
Abstract There are complex potential inter-relationships between the chronic inflammation of asthma and poor control, vitamin D deficiency, musculoskeletal pain and anxiety and depression. The aim was to investigate associations between vitamin D and these possible co-morbidities. This case-controlled study involved 75 adults with asthma and 75 controls. Serum 25-hydroxyvitamin D (25(OH)D) was measured, levels of anxiety, depression, musculoskeletal pain, and asthma control were assessed. Participants with asthma had lower 25(OH)D and higher anxiety scores and higher measures of musculoskeletal pain compared to controls. Binary logistic regression showed that asthma was associated with decreased 25(OH)D (Odds ratio (OR) = 0.86), general weakness (OR = 13.29), complaint of musculoskeletal pain (OR = 13.73), and increased intensity of musculoskeletal pain (OR = 0.61) and number of painful sites (OR = 2.58). Asthma was not associated with anxiety or depression. Further studies are required to investigate if vitamin D supplementation can improve asthma symptoms and musculoskeletal pain.